The Northern Irish Party System after the Good Friday Agreement (Comillas Journal of International Relations, 2020)
The aim of this work is to analyze the way in which the Good Friday Agreement, signed in 1998 and that consolidated the Peace Process which ended the period of violence suffered by the region during its last three decades, has affected the Northern Irish party system. We will try to confirm our hypothesis, which claims that the Agreements have favored those parties whose discourse was more extremist. Nevertheless, we will also try to prove that the rising of those parties was accompanied by a moderation of its discourse. To reach this aim we will analyze the impact of the institutional framework on that process. This analysis will be done under the theoretical perspective of consotionalism.
Keywords: Northern Ireland; consotionalism; nationalism; conflict resolution; centrifugalism